Sharia Banking Strategy in Improving Gross Regional Domestic Products in Sambas District, Indonesia - Sri Deti; Oskar Hutagaluh; Hadenan Towpek (IQTISHODUNA: Jurnal Ekonomi Islam, 2021)
The low contribution of Sharia Banking to the growth rate of Gross Regional Domestic Product for seven years is present in the midst of the people of Sambas Regency, who in fact are the majority of Muslims, so it requires an effort to be able to make a bigger contribution. This study aims to formulate any strategies required by Islamic banking in order to increase the Gross Regional Domestic Product of Sambas Regency with a descriptive quantitative approach. Based on the results of the SWOT analysis and continued with the Quantitative Strategic Planning Matrix (QSPM) analysis, there are seven alternative strategic sector development priorities that can be carried out by Islamic banking in order to increase the Gross Regional Domestic Product of Sambas Regency. Based on the assessment of strategic attractiveness, it shows that the most attractive strategy to be implemented is to collaborate with local governments and institutions in society, then follow the strategy of improving the quality of human resources and technology in the second position and then socializing the advantages of Islamic banking to all levels. community, expand networks, determine superior financing products, be active in financing management, and streamline educational, socialization and promotion activities to gather customers.